Insights into early winter Southern Indian Ocean dissolved iron distributions and remineralisation using excess barium (GEOTRACES GIPr07 cruise) - Van Horsten, Natasha (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.